Superconducting behavior of amorphous Zr70Cu30 - Arce, R.; de la Cruz, F.; Guimpel, J.; Guimpel, Julio (Elsevier, 1983)
Fil: Arce, R. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina